2002
DOI: 10.1194/jlr.m200271-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Lack of stearoyl-CoA desaturase-1 function induces a palmitoyl-CoA Δ6 desaturase and represses the stearoyl-CoA desaturase-3 gene in the preputial glands of the mouse

Abstract: The mouse preputial gland (PG), a specialized sebaceous structure, is rich in wax esters, triglycerides, and alkyl-2,3-diacylglycerol. We have found that the mouse PG expresses the three gene isoforms (SCD1, SCD2, and SCD3) of the ⌬ 9 stearoyl-CoA desaturase enzyme that catalyzes the biosynthesis of monounsaturated fatty acids mainly, C16:1n-7 and C18:1n-9. However, mice with a targeted disruption in the SCD1 isoform (SCD1 ؊ / ؊ ) have undetectable SCD3 mRNA expression in the PG while the expression of SCD2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 24 publications
3
45
0
2
Order By: Relevance
“…This result assesses that a high level of ⌬6-desaturase expression simultaneously allows the ⌬6-desaturation of C16:0 and C18:3 n-3. However, Miyazaki and coworkers (1) suggested that the conversion of C16:0 to C16:1 n-10 could be performed by an enzyme distinct from FADS2. From our study, it appears unlikely that an additional enzyme desaturates C16:0 to C16:1 n-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result assesses that a high level of ⌬6-desaturase expression simultaneously allows the ⌬6-desaturation of C16:0 and C18:3 n-3. However, Miyazaki and coworkers (1) suggested that the conversion of C16:0 to C16:1 n-10 could be performed by an enzyme distinct from FADS2. From our study, it appears unlikely that an additional enzyme desaturates C16:0 to C16:1 n-10.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a palmitoyl-CoA ⌬ 6-desaturase has recently been described in mice (1). This unexpected ⌬ 6-desaturase activity was found in mice deficient for stearoyl-CoA desaturase 1 (SCD1 Ϫ / Ϫ mice).…”
mentioning
confidence: 99%
“…While mouse SCD1 is expressed at high levels in adipose tissue and is induced in liver under high-carbohydrate conditions, SCD3 expression is restricted to skin, Harderian gland, and the preputial gland (17)(18)(19). We took advantage of the substrate preferences of distinct SCD isoforms to restore oleate (human SCD5) or palmitoleate (mouse SCD3) synthesis in the liver only in GKO mice.…”
Section: Liver Histologymentioning
confidence: 99%
“…Exogenous saturated fatty acids (0.2 mM) were added into YPD in the presence of 1% Tergitol NP-40 (Sigma). The double bond positions of the monounsaturated fatty acid methyl ester were determined by GC-MS analysis of the dimethyl disulfide derivatives (11,22).…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…SCD2 is expressed primarily in the brain and neuronal tissue, particularly during the neonatal mylenation period (6). SCD3 expression is restricted to sebocytes in skin, preputial gland, and Harderian gland (9)(10)(11). SCD4 is expressed predominantly in heart (7).…”
mentioning
confidence: 99%